A metabolomics approach for investigating urinary and plasma changes in spontaneously hypertensive rats (SHR) fed with chicken skin protein hydrolysates diets. (April 2016) - Onuh, John O.; Girgih, Abraham T.; Nwachukwu, Ifeanyi; Ievari-Shariati, Shiva; Raj, Pema; Netticadan, Thomas; Aluko, Rotimi E.; Aliani, Michel
Highlights: Chicken skin peptides reduced plasma angiotensin converting enzyme levels in SHR. Metabolomics profile revealed distinct urinary and plasma metabolites of hypertension. SHR urinary uric acid level was down-regulated by the peptide treatment. SHR urinary N2 -acetyl-L-ornithine was down-regulated in the treated groups. Urinary buthionine sulfoximine (a prooxidant) was reduced in the treated SHR. Abstract: Plasma and urine metabolomics profiles of spontaneously hypertensive rats (SHRs) fed with chicken skin protein hydrolysates (CSPHs) were investigated to establish possible biomarkers of blood pressure regulation. SHR and wistar Kyoto (WKY) rats were randomised into groups that received casein-only (control), CSPHs (0.5 or 1%) or chicken skin meal (CSM 1%) diets for six weeks. Results showed that the diets significantly (P < 0.05) lowered systolic blood pressure (SBP) of SHRs (−36, −31 and −26 mmHg for CSPH 1%, CSPH 0.5% and CSM 1%, respectively) but not WKY. This correlated with decreased plasma angiotensin converting enzyme levels but not with superoxide dismutase activity. Partial least square discrimination analysis of detected metabolites in urine and plasma of rats showed significant changes in levels of symmetric dimethylarginine, N2 -acetyl-L-ornithine, buthionine sulfoximine, uric acid, α-tocopherol succinate, L-isoleucine, creatinine, and phospholipids. CSPHs could therefore be used as ingredients in developing nutraceuticals and functional foods for hypertension management.